Lebrikizumab - Rob, Filip (Remedia, 2024)
x
Keywords: klinické zkoušky jako téma; inhibitory interleukinu; lebrikizumab; studie ADhere; biologická terapie; studie ADvocate 1; výsledek terapie; analýza dat; Injections, Subcutaneous; Biological Therapy; Dermatitis, Atopic; Clinical Trials as Topic; Interleukin Inhibitors; Humans; Data Analysis; studie ADore; atopická dermatitida; injekce subkutánní; studie ADvocate 2; Treatment Outcome; lidé